Performance improvement of wavelength division multiplexing passive Optical networks for SCADA - ahmed abd Raouf Aiche (My University, 2024)
This master thesis presents a comprehensive examination of the integration possibilities between SCADA (Supervisory Control and Data Acquisition) systems and Passive Optical Networks (PON), aiming to unlock synergies and optimize industrial communication and networking solutions. Beginning with an exhaustive analysis of SCADA systems, it delves into the core components such as Human-Machine Interface (HMI), Supervisory Systems, Remote Terminals, and Programmable Logic Controllers (PLCs), while addressing critical data transmission challenges. Subsequently, the study explores the realm of fiber optics, elucidating their composition, types, and characteristics, before transitioning to an in-depth investigation of Passive Optical Networks, including their architecture, standards, and benefits. Leveraging OptiSystem software, the thesis conducts simulations to evaluate the optical transmission chain of PON systems, focusing on the impact of chromatic dispersion and various compensation techniques. Through meticulous analysis and comparative assessments, this master thesis provides valuable insights and recommendations for the seamless integration and optimization of SCADA systems and PON networks, thereby contributing to the advancement of industrial automation and optical communication technologies. ----------------------------------------------------------------------------------------------- تقدم أطروحة الماستر هذه فحصًا متعمقًا لإمكانيات التكامل بين أنظمة التحكم الإشرافي والحصول على البيانات (SCADA) والشبكات الضوئية المنفعلة (PON)، والتي تهدف إلى فتح أوجه التآزر وتحسين حلول الاتصالات والشبكات الصناعية. بدءًا من التحليل الشامل لأنظمة SCADA، فإنه يتعمق في المكونات الأساسية مثل واجهة الإنسان والآلة (HMI)، والأنظمة الإشرافية، والمحطات الطرفية عن بعد، وأجهزة التحكم المنطقية القابلة للبرمجة (PLC)، مع معالجة تحديات نقل البيانات الهامة. بعد ذلك، تستكشف الدراسة مجال الألياف الضوئية، وتوضح تركيبها وأنواعها وخصائصها، قبل الانتقال إلى بحث متعمق في الشبكات الضوئية المنفعلة، بما في ذلك بنيتها ومعاييرها ومزاياها. باستخدام برنامج OptiSystem، تجري الأطروحة عمليات محاكاة لتقييم سلسلة النقل البصري لأنظمة PON، مع التركيز على تأثير التشتت اللوني وتقنيات التعويض المختلفة. من خلال التحليل الدقيق والتقييمات المقارنة، توفر رسالة الماجستير هذه رؤى وتوصيات قيمة للتكامل السلس وتحسين أنظمة SCADAوشبكات PON، وبالتالي المساهمة في تقدم الأنظمة الصناعية وتقنيات الاتصالات البصرية. --------------------------------------------------------------------------------------------- Cette thèse de master présente un examen approfondi des possibilités d'intégration entre les systèmes SCADA (Supervisory Control and Data Acquisition) et les réseaux optiques passifs (PON), visant à débloquer des synergies et à optimiser les solutions de communication et de réseau industrielles. À partir d'une analyse exhaustive des systèmes SCADA, elle explore les composants essentiels tels que l'Interface Homme-Machine (HMI), les systèmes de supervision, les terminaux distants et les contrôleurs logiques programmables (PLC), tout en abordant les défis critiques de transmission des données. Ensuite, l'étude explore le domaine des fibres optiques, en élucidant leur composition, leurs types et leurs caractéristiques, avant de passer à une investigation approfondie des réseaux optiques passifs, y compris leur architecture, leurs normes et leurs avantages. En utilisant le logiciel OptiSystem, la thèse réalise des simulations pour évaluer la chaîne de transmission optique des systèmes PON, en se concentrant sur l'impact de la dispersion chromatique et des différentes techniques de compensation. Grâce à une analyse méticuleuse et à des évaluations comparatives, cette thèse de master fournit des insights précieux et des recommandations pour l'intégration et l'optimisation sans faille des systèmes SCADA et des réseaux PON, contribuant ainsi à l'avancement des technologies d'automatisation industrielle et de communication optique.